Akibat Hukum Mou Impor Beras Indonesia - Thailand Berdasarkan Hukum Perdagangan Internasional - Carissa Amanda Siswanto; Dita Birahayu (Universitas Merdeka Madiun, 2022)
Abstract –The MoU is often used as a prelude before an agreement is reached between the two countries. To date, there are no regulations that specifically require the MoU to be legally incorporated into law. The research method used is normative juridical, namely through literature studies by reviewing various legal theories and laws and regulations (law in books). It is then analyzed by prioritizing secondary data as primary and secondary laws. The results of this study show that, the Indonesian and Thai MoUs on rice imports in 2021 is an agreement, the MoU is based on the strength of an agreement and the fundamental principle of treaty law as set out in Vienna Convention of 1969. Any agreements made apply legally to their creators. The signing of the MoU on rice imports in 2021 has binding and coercive powers for both countries. If one of the countries violates the MoU, then the aggrieved country may refer to the choice of law.